A mixed integer programming formulation and effective cuts for minimising schedule durations of Australian truck drivers - Goel, Asvin (Journal of scheduling, 2012)
Transport companies seek to maximise vehicle utilisation and minimise labour costs. Both goals can be achieved if the time required to fulfil a sequence of transportation tasks is minimised. However, if schedule durations are too short drivers may not have enough time for recuperation and road safety is impaired. In Australia transport companies must ensure that truck drivers can comply with Australian Heavy Vehicle Driver Fatigue Law and schedules must give enough time for drivers to take the amount of rest required by the regulation. This paper shows how transport companies can minimise the duration of truck driver schedules complying with Australian Heavy Vehicle Driver Fatigue Law. A mixed integer programming formulation is presented and valid inequalities are given. Computational experiments show that these inequalities provide significant reduction in computational effort when using one of the most advanced commercial mixed integer programming solver.